The Quality of higher education in the Philippines with the establishment of the commission on higher education - Bernaldez, Corinne V (KDI School, 2011)
Studies have shown that education is important in the development of a country. On average, countries with higher levels of education and skill boast of higher levels of productivity and economic growth. Recognizing this, the 1992 Congressional Commission on Education created two more agencies, the Commission on Higher Education and the Technical Education, Skills and Development Authority, to help the Department of Education in strengthening education/training activities to meet labor market and social demands of the future. This study looks at the effect of CHED on the quality of higher education after more than a decade of existence using four quality indicators namely: (1) performance of students in board exams, (2) status of program accreditation, (3) employability of graduates, and (4) faculty profile. Previous studies were reviewed and statistical data from CHED were analyzed to observe if there have been improvements since the creation of CHED. Although there were moderate gains in the number of faculty with master and doctoral degrees, and the number programs that have been accredited, these were counteracted by the almost double increase in the number of higher education institutions in the country. Overall, no significant improvements could be discerned from the four quality indicators.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Philippine.